Evaluation of Zn, Cu, and Se Levels in the North American Autism Spectrum Disorder Population - Mehta, Sunil Q.; Behl, Supriya; Day, Patrick L.; Delgado, Adriana M.; Larson, Nicholas B.; Stromback, Lindsay R.; Huebner, Andrea R.; DeGrado, Timothy R.; Davis, Jessica M.; Jannetto, Paul J.; Howie, Flora; Pandey, Mukesh K. (Frontiers in Molecular Neuroscience, 2021)
Metal ion dyshomeostasis and disparate levels of biometals like zinc (Zn), copper (Cu) and selenium (Se) have been implicated as a potential causative factor for Autism Spectrum Disorder (ASD). In this study, we have enrolled 129 children (aged 2-4 years) in North America, of which 64 children had a diagnosis of ASD and 65 were controls. Hair, nail, and blood samples were collected and quantitatively analyzed for Zn, Cu and Se using inductively coupled plasma mass spectrometry (ICP-MS). Of the analyzed biometals, serum Se (116.83±14.84 mcg/mL) was found to be significantly lower in male ASD cases compared to male healthy controls (128.21 ±9.11 mcg/mL; p < 0.005). A similar trend was found for nail Se levels in ASD (1.01±0.15 mcg/mL) versus that of controls (1.11±0.17 mcg/mL) with a p value of 0.0132 using a stratified Wilcoxon rank sum testing. The level of Se in ASD cohort was co-analyzed for psychometric correlation and found a negative correlation between total ADOS score and serum Se levels. However, we did not observe any significant difference in Zn, Cu and Zn/ Cu ratio in ASD cases versus controls in this cohort of North American children. Further studies are recommended to better understand the biology of the relationship between Se and ASD status.